PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN TRANSAKSIONAL TERHADAP KINERJA BAWAHAN MELALUI KEPUASAN KERJA - Sardi Sardi (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2017)
The purpose of this study is to investigate whether transformational and transactional leadership styles have an impact on subordinate performance. Also we want to analyze the effect of job satisfaction as a mediating role.The study was conducted at SMK Muhammadiyah Pakem and SMK Muhammadiyah 1Moyudan, Sleman. The number of samples was  110 respondents(teachers and school employees).  Structural Equation Modeling (SEM) analysis was used to analyze the data. The results showed that the transformational leadership style did not have a significant influence on subordinate performance while transactional one influenced positively. The transformational leadership style had a significant influence on job satisfaction. The result of the transactional leadership style on job satisfaction was  negative, while job satisfaction had a very significant influence on subordinate performance. Based on these studies, it was recommended that the principal should apply a combination of both Transformational and Transactional leadership styles in accordance with the situation and the nature of the particular task assigned to the employee. In addition,  Transactional leadership style is more preferable in improving employee performance to reach optimal organizational performance.